PENGARUH ASIMETRI INFORMASI, LEVERAGE, UKURAN PERUSAHAAN DAN KEPEMILIKAN MANEJERIALTERHADAP EARNINGS MANAGEMENT - Yogi Hady Afrizal; Mursalim Mursalim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This research focused on the profit of one source of information used by investors to take decision before investing in a company. But, they did not think of a way and the process of the creating these profits. This has been one of the cause of investor gets missinformation of a candidate company places they would invest.This research applied quantitative method in revealing the data, using secondary data in the form of financial statement. Population in this research derived from Stock Indonesian Exhange (BEI) in Index LQ-45 since 2015-2017. The analysis technique of data used in this research was multiple regression analysis technique.The researcher concluded that the testing of hypotheses in the research indicated that asimetry information, leverage, and managerial ownership significant and positive of earnings management, while the firm size not significant and negative of earnings management.